Design of Low-Power 2.5 GHz Integer-N Frequency Synthesizer - A. Raheem, M.; Shaik, Subhanvali; Majid, Abdul; ur Rehman, Suhaib; Arif, Syed (International Journal of Engineering and Technology, 2018)
In this context a low powered, N-Integral frequency synthesizer of 2.5GHz for RF applications is proposed. Corroboration of concept is established by implementing the design of frequency synthesizer circuit in 180nm CMOS technology. The frequency generated by the synthesizer ranges from 2.4GHz to 2.5GHz and power consumption is 5.54mW from a 1.8V power supply. This synthesizer is found to have a phase noise of -95.15dBc/Hz at an offset of 1MHz from the carrier.Â Â Â